A study of insider threat behaviour: developing a holistic framework - Munshi, Asmaa (IADIS press, 2010)
This research aims to develop a holistic view of insider threat behaviour and ways to manage it. This research will be conducted by data collection in three phases: academic research sources published legal cases, and managment and business sources. The study results will develop insider threat behaviour model. This model will be assessed by focus group prior to building the framework. Later, a management framework will be developed to manage insider threat behaviour. Finally, to ensure the practicality of the new framework a focus group will assess the management framework.